The Use of Chat GPT Platform as a Learning Medium to Improve Maharah Kalam - Setiawati, Anandita Galuh; Hanifah, Umi; Alfisyah, Alfisyah (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The rapid development of technology in the era of the Fourth Industrial Revolution has significantly transformed education, including the teaching of Arabic as a foreign language. Arabic holds both academic and religious importance and requires mastery of four language skills (maharah), with speaking (maharah kalam) being one of the most challenging. This article presents the analysis of the use of ChatGPT as an adaptive learning medium to improve the speaking skills of tenth-grade students at Sekolah Indonesia Jeddah. Using a qualitative descriptive approach with an analytical perspective, the data were collected through classroom observation and semi structured interviews with Arabic language teachers and selected students’ outputs. The findings indicated that ChatGPT can serve as an interactive tool that allows students to practice dialogues, receive instant feedback, and build motivation to learn outside classroom hours. The analysis showed that while ChatGPT effectively supports students’ speaking proficiency, its optimal use depends on clear learning objectives, well designed conversation themes, and continuous teacher guidance. Limitations remain, such as occasional linguistic inaccuracies, lack of nonverbal elements, and the risk of student dependency. Therefore, teachers played a crucial role in guiding, monitoring, and motivating students to ensure effective use of ChatGPT. Overall, ChatGPT can be positioned as a complementary medium that enriches students’ learning experiences and supports the development of maharah kalam, while also contributing to innovation in Arabic language education in the digital era.